Global, regional, and national burdens of chronic kidney disease attributable to high body mass index from 1990 to 2021, with future forecasts up to 2050: a systematic analysis for the global burden of disease study 2021 - Jun Ying; Xiaolei Lan; Hanjing Zhou; Hongxia Li; Weixin Sheng; Jian Huang (Frontiers in Public Health, 2025)
BackgroundHigh body mass index (BMI) is a major modifiable risk factor for the development and progression of chronic kidney disease (CKD) through established mechanisms, including glomerular hyperfiltration and metabolic dysfunction. This study aimed to characterize the global, regional, and national temporal trends in CKD attributable to BMI from 1990 to 2021 and forecast trends up to 2050.MethodsData were obtained from the Global Burden of Disease 2021 Study. Deaths and disability-adjusted life years (DALYs) for patients with CKD attributable to a high BMI were analyzed using age-standardized rates. The estimated annual percentage change was then calculated. Attribution was calculated as the product of the population-attributable fractions (PAFs) related to CKD deaths/DALYs and disease burden, with deaths/DALYs as the unit of measurement. Age-period cohort analysis was used to estimate the age, period, and cohort effects. Bayesian age-period-cohort modeling was used to predict the burden of CKD associated with high BMI from 2021 to 2050.ResultsFrom 1990 to 2021, the burden of CKD attributable to BMI showed an increasing trend. Age-standardized death and DALY rates increased in all Sociodemographic Index regions from 1990 to 2021. At the national level, most countries have exhibited an increase in burden from 1990 to 2021. Among females, the 85–89 age group had the highest number of deaths (28,478), whereas among males, it was the 70–74 age group (25,270). Globally, high BMI is a risk factor for CKD, contributing to 27.3% of deaths. With respect to the age effect, deaths from CKD attributable to high BMI increased with age. The burden of CKD attributable to high BMI generally increases from 2021 to 2050.ConclusionThe burden of CKD attributable to high BMI increased significantly between 1990 and 2021. The growing global burden demands urgent and mechanistically informed health interventions that target the complex pathophysiology of obesity-related kidney diseases.